Social Media Analysis Of Service Quality And Its Implications For Blood Donor Interest At The Indonesian Red Cross Sidoarjo Blood Transfusion Unit In Sidoarjo Regency - Nunuk Masluhiyah; Vip Paramarta; Rahadian Malik (LP2M IAIN Palopo, 2026)
The Sidoarjo Regency Indonesian Red Cross Blood Donor Unit is a blood service unit that functions as a blood donor service facility, blood supply, and blood distribution. The demand for blood is disproportionate to the number of people in need, due to a lack of information and public awareness of voluntary blood donation. In 2024, the number of requests for blood was only 66.99%. This indicates that the Sidoarjo Regency Indonesian Red Cross is unable to meet the demand for blood according to community needs. This study aims to analyze the influence of social media on the quality of service that has implications for the interest of blood donors at the BDU PMI Sidoarjo Regency in 2025. This type of research is quantitative, with the number of research subjects being some blood donors at the BDU PMI Sidoarjo Regency, on December 1-15, 2025, as many as 96 people. Analysis used is path analysis, correlation coefficient and determination coefficient. The results of the study showed that there was an influence of mass media (X) on the quality of service (Y) which had implications for the interest in blood donation (Z) simultaneously with a ρ value of 0.000 < 0.05, and or the F-count value > F-table (207.121> 3.94), and there was an indirect influence of mass media (X) on the interest in blood donation (Z) through the quality of service (Y) with a statistical test value of 3.932 and a ρ value of 0.000 < 0.05. Therefore, it is recommended that the BDU PMI Sidoarjo Regency improve the quality of blood donor services, comfort, clarity in conveying blood donor information, friendliness and politeness in services and handling complaints quickly and appropriately, so that it can increase donor interest in donating blood and invite people around them to donate blood.